ABANDONMENT OF RIGHTS TO MINERALS GRANTED IN TERMS OF THE MINERAL AND PETROLEUM RESOURCES DEVELOPMENT ACT - Cramer, Richard (Obiter, 2023)
A peculiar feature of the Mineral and Petroleum Resources Development Act (MPRDA) is the mention of the possibility of abandoning rights granted in terms of its provisions. It has been commented by Van der Schyff that the possibility of abandoning these rights is inconsistent with the Act’s objectives of the MPRDA. In particular, empowering a right-holder to abandon a right granted in terms of the MPRDA fails to take into account that such a right comes with significant responsibilities and obligations. As such, unilateral abandonment should not be possible in terms of the legal framework created by the MPRDA.This article seeks to address this peculiarity in the MPRDA. It considers the legislative context in which such an abandonment (if possible) would operate. The analysis of the possibility of abandoning rights granted in terms of the MPRDA is undertaken in light of theoretical observations in respect of the abandonment of property rights, in particular the seminal article on the subject by Peñalver. The article seeks to answer the question as to whether abandonment, as envisaged by the MPRDA, is possible in the legal framework the Act creates, and outlines the potential consequences thereof for the would-be abandoner.